The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1097/pcc.0b013e31823893ad
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and comparison of parental needs, stressors, and coping strategies in a pediatric intensive care unit

Abstract: Acute parental experiences can be documented using the COMPASS questionnaire. This study highlights the principal needs, stressors, and coping strategies of parents of children in the pediatric intensive care unit. The experiences of mothers and fathers are similar, but we identify some differences in stressors between the sexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 36 publications
1
42
2
Order By: Relevance
“…The environment has been noted as one of parents' stressors during their child's critical care admission (Carnevale, 1990;Jee, et al, 2012). Compared with previous studies, this current study has revealed different findings as the parent participants placed more emphasis upon the environment, linking their ability to achieve comfort to the environment of the hospital units.…”
Section: The Environment Makes a Differencecontrasting
confidence: 53%
See 4 more Smart Citations
“…The environment has been noted as one of parents' stressors during their child's critical care admission (Carnevale, 1990;Jee, et al, 2012). Compared with previous studies, this current study has revealed different findings as the parent participants placed more emphasis upon the environment, linking their ability to achieve comfort to the environment of the hospital units.…”
Section: The Environment Makes a Differencecontrasting
confidence: 53%
“…Getting the perspective from the whole family is very important in familycentered care, because mothers and fathers may experience stress differently and have different needs while in PICU. For example, Jee et al (2012) found that mothers needed to participate in care, be informed about the transfer, and be informed of changes in their child's condition significantly more often than fathers. Jee et al also noted statistically significant differences between mothers and fathers in terms of the emphasis placed on the ability to care for the child, the child's looks, and reactions to the procedures or leaving the child.…”
Section: Limitations Of Current Literature On Parental Transitionsmentioning
confidence: 99%
See 3 more Smart Citations